27Al MQMAS of the δ-Al13-Keggin. Issue 7 (27th January 2017) - Pilgrim, C. D.; Callahan, J. R.; Colla, C. A.; Ohlin, C. A.; Mason, H. E.; Casey, W. H.
Abstract : 27 Al-MQMAS spectra of the δ isomer of the Na[AlO4 Al12 (OH)24 (OH2 )12 ]·2, 6-napthalene disulfonate salt. Abstract : One-dimensional 27 Al, 23 Na Magic-Angle-Spinning (MAS) NMR and 27 Al Multiple-Quantum Magic-Angle-Spinning NMR (MQMAS) measurements are reported for the δ-isomer of the Al13 Keggin structure at high spinning speed and 14.1 T field. Values for the C Q and η parameters are on the same scale as those seen in other isomers of the Al13 structure. Density functional theory (DFT) calculations are performed for comparison to the experimental fits using the B3PW91/6-31+G* and PBE0/6-31+G* levels of theory, with the Polarizable Continuum Model (PCM).